SHAPING MODERN CULTURE: THE IMPACT OF MEMES AND INTERNET SLANG - I Gede Widya Suputra; Suci Pole Mappaita (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
This study explores the contribution of memes and internet slangs to the construction of modern cultural identity in virtual communities. As social media emojis language like X, TikTok and Instagram continue to be integral components of communication people start to create and use memes and slangs that even surpasses casual talk. These are lines that communicate shared values, shared humour, shared resistance, and shared membership with others. This article provides qualitative content analysis, inquiring into the nature and uses of these terms. The results show that memes and slangs is a cultural marker that affects how people create groups, define their identities, and interact with others online. The relationship between identity politics and language innovation in digital contexts is also examined in this study. The work adds to sociolinguistics and digital cultural studies by analysing how language changes in real-time via virtual encounters, highlighting the significance of meme and slangs as a potent, dynamic form of cultural expression.